Induced third-degree burn in rat: healing by Melilotus officinalis extract as medicinal plant - Nader Tanideh; Omid Safa; Saeedeh Kheradmand; Mohammad Mehdi Zarshenas; Maral Mokhtari; Omid Koohi Hosseinabadi; Anahita Seddighi; Akram Jamshidzadeh; Babak Shirazi Yeganeh; Mahmoud Omidi; Sajad Daneshi (Shiraz University of Medical Sciences, 2018)
Introduction: burn wounds are common happenings which cause many people have irreversible defects and to be death around the world every year.  In this study, we evaluated the effects of Melilotus officinalis and Alpha ointment in the healing of burn wounds and compare their findings with silver sulfadiazine (SSD).Methods: Seventy-five male Sprague-Dawley rats were randomly divided into five groups, and similar burn ulcers were produced on the back of rats. The first group of rats received no treatment, base gel was used topically to group II, in groups III-V, Alpha, SSD and Melilotus officinalis preparations were applied, respectively. Wound healing, contraction and histopathological examination were evaluated at the end of 7, 14, and 21 days.Results: Alpha ointment was equally effective as Melilotus officinalis gel, while its efficacy was better compared to SSD for all parameters of wound healing on days 7, 14 and 21. Alpha and Melilotus officinalis preparations as less expensive medications which significantly improve the quality of wound healing and scar formation and also are more appropriate treatment choices than SSD.Conclusion: Alpha and Melilotus officinalis are recommended as alternative to SSD, especially in patients with low economical backgrounds or in those who show adverse reactions to SSD.